Analysis of Factors Affecting Premature Labor in Pregnant Women Based on Various Health and Environmental Aspects - Hasriah Hasriah; Rifzul Maulina; Widia Shofa Ilmiah (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Preterm birth, defined as birth before 37 weeks of gestation, is a significant global health problem, with rising rates in many regions worldwide. The World Health Organization (WHO) reports that approximately 15 million babies are born prematurely every year, and this number continues to increase. Preterm birth is a major contributor to neonatal morbidity and mortality, making it an urgent issue for public health. This study aims to explore the various factors influencing the occurrence of preterm birth, including medical, social, and environmental factors. The study employed an observational analysis with a case-control design to identify and analyze these factors. Data were collected from medical records of deliveries that took place between January and December 2024. The study used a total sample size of 100 participants, consisting of 50 cases of preterm birth and 50 control cases. The control group was selected using simple random sampling to ensure unbiased selection. The data were analyzed using the chi-square test, and logistic regression was applied to assess the strength of the relationships between identified factors and the occurrence of preterm birth. The findings of this study indicate that several factors significantly contribute to the likelihood of preterm birth, including parity, pregnancy spacing, infections, and blood pressure (p-value < 0.05). These factors were found to increase the risk of preterm birth. The study concludes by emphasizing the need for early intervention to identify and manage these risk factors, thus minimizing the incidence of preterm birth. It is also recommended that pregnant women receive education and support programs aimed at reducing risk factors. Further research, especially longitudinal studies, is suggested to explore the mechanisms underlying preterm labor and to develop more effective preventive strategies.